The Effect of Work Family Conflict on Employee Performance with Work Life Balance as an Intervening Variable during the Covid-19 Pandemic: Case Study on Employee of PT Jasa Marga Toll Road Operator, Semarang and Batang Branches - Dian Puspitasari; Intan Ratnawati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze how much influence the work family conflict variable has on employee performance through work life balance as an intervening variable owned by employees of PT Jasa Marga TollRoad Operator Semarang and Batang Branches. The data used in this study are primary data derived from the distribution of research questionnaires. The population of this study used permanent and married employees from the top and middle line management levels at PT Jasa Marga TollRoad Operator Semarang ABC Branch with a total of 52 people and PT Jasa Marga TollRoad Operator Batang Branch - Semarang with a total of 34 people. So that the total population in this study amounted to 86 people. This research uses Partial Least Square (PLS) analysis technique with SmartPLS software analysis tool.  The findings show that work family conflict has a negative effect on employee performance, work family conflict has a negative effect on work life balance, work life balance has a positive effect on employee performance and work life balance mediates work family conflict on employee performance. Based on this research, it means that work family conflict needs to be reduced in order to improve employee performance at the top and middle line management levels of PT Jasa Marga TollRoad Operator Semarang and Batang. In addition, the work life balance needs to be improved in order to improve employee performance at the top and middle line management levels of PT Jasa Marga TollRoad Operator Semarang and Batang